2022
DOI: 10.1093/braincomms/fcac303
|View full text |Cite
|
Sign up to set email alerts
|

Implicit sensorimotor adaptation is preserved in Parkinson’s disease

Abstract: Our ability to enact successful goal-directed actions involves multiple learning processes. Among these processes, implicit motor adaptation ensures that the sensorimotor system remains finely tuned in response to changes in the body and environment. Whether Parkinson’s disease impacts implicit motor adaptation remains a contentious area of research: whereas multiple reports show impaired performance in this population, many others show intact performance. While there is a range of methodological differences a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Given that adult-onset motor speech disorders progress in concert with general physiological declines in speech-related subsystems, such as oromotor muscle strength (Baum & Bodner, 1983;Robbins et al, 1995) and auditory acuity (Cruickshanks et al, 1998;Gadkaree et al, 2016), we included participants across the lifespan and found no evidence that formant adaptation is limited by healthy aging. At present, it seems that sensorimotor adaptation of speech is relatively preserved across the lifespan as well as (if somewhat diminished) in dysarthria (Mollaei et al, 2013;Mollaei et al, 2016;Polsterer, 2024; see also Tsay et al, 2022 andBock &Schneider, 2002). Together, this evidence suggests that sensorimotor adaptation to vowel centralization may benefit persons who present with reduced vowel spaces.…”
Section: Discussionmentioning
confidence: 94%
“…Given that adult-onset motor speech disorders progress in concert with general physiological declines in speech-related subsystems, such as oromotor muscle strength (Baum & Bodner, 1983;Robbins et al, 1995) and auditory acuity (Cruickshanks et al, 1998;Gadkaree et al, 2016), we included participants across the lifespan and found no evidence that formant adaptation is limited by healthy aging. At present, it seems that sensorimotor adaptation of speech is relatively preserved across the lifespan as well as (if somewhat diminished) in dysarthria (Mollaei et al, 2013;Mollaei et al, 2016;Polsterer, 2024; see also Tsay et al, 2022 andBock &Schneider, 2002). Together, this evidence suggests that sensorimotor adaptation to vowel centralization may benefit persons who present with reduced vowel spaces.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, the computer mouse has been used as a valid tool to study motor adaptation and sensorimotor learning ( Lee et al, 2016 ; Avraham et al, 2021 ; Listman et al, 2021 ; Tsay et al, 2021 , 2023 ; Balestrucci et al, 2022 ; Donovan et al, 2022 ; Weightman et al, 2022 ) across a wide age range from 18 to 70 ( Tsay et al, 2023 ). It has been found such data collected through computer mouse are reliable, valid, and able to reproduce classic findings as in the literature examined 3D real-world hand movements, even among children between 9 and 16 ( Malone et al, 2023 ), older people with and without Parkinson’s disease ( Tsay et al, 2022 ) and individuals with impaired visual function ( Tsay et al, 2023 ).…”
Section: Introductionmentioning
confidence: 81%
“…Studies of sensorimotor adaptation are typically conducted with specially designed apparatuses in controlled laboratory settings. This approach has been extremely successful in revealing critical spatial (17)(18)(19)(20) and temporal (21)(22)(23)(24)(25) constraints on adaptation, as well as examining the contributions of different neural systems to this form of learning (1,2,12,(26)(27)(28)(29)(30)(31)(32). However, in-person research typically involves small, homogenous samples (33), making certain research questions impractical and difficult to answer (e.g., exploring how different demographic factors modulate motor behavior).…”
Section: Introductionmentioning
confidence: 99%